The effectiveness of distance learning initiatives in organizations - Burgess, Jennifer R. D. [Verfasser]; Russell, Joyce E. A. [Verfasser] (My University, 2003)
"Today, organizations are increasingly adopting distance learning methods to train and develop their employees. Despite the widespread use of these methods, little research has been done regarding their effectiveness. The present paper reviews current literature on the effectiveness of distance learning methods in terms of employees' reactions, learning, behavior, and organizational results. Suggestions for future research and practice are also offered." (author's abstract, IAB-Doku) ((en))
Keywords: L 4.2.3 Internetbasiertes Lernen / E-Learning; L 2.3 Methoden; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; S 3.2 Unternehmen und Behörden; Berufliche Weiterbildung; E-Learning; Personalentwicklung; Ausbildungsmethode; Arbeitnehmer; Verhalten; Unternehmen